Studi in Silico Senyawa Fitokimia Daun Ketepeng Cina (Cassia alata) sebagai kandidat antibakteri Staphylococcus aureus Penyebab Impetigo - Sintya; Dora Dayu Rahma Turista; Elsje Theodora Maasawet; Risty Geofani; Miningsih; Rusni Ernopita Ulan; Dorce Bani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the potential of phytochemical compounds from Cassia alata leaves — emodin, chrysophanol, rhein, kaempferol, quercetin, and physcion — as antibacterial candidates against the FtsZ protein (Staphylococcus aureus, PDB ID: 4DXD), the cause of impetigo. The method used was molecular docking. The results showed that kaempferol had the best binding affinity (-9.6 kcal/mol), followed by rhein and quercetin (-9.2 kcal/mol), with key interactions consisting of hydrogen bonds at residues THR309, ASN263, and GLY196, as well as hydrophobic interactions at residues LEU200 and VAL297. All compounds complied with Lipinski's Rule of Five (0 violations, bioavailability 0.55–0.56) and were non-carcinogenic, although some showed hepatotoxicity potential (LD50 1190–5000 mg/kg, class IV–V); bioactivity prediction further confirmed high antibacterial potential. In conclusion, kaempferol and rhein were recommended as promising candidates for further verification, given the existing resistance to antibiotics such as levofloxacin. Keywords: Cassia alata, FtsZ, Kaempferol, Molecular Docking